Efficacy and safety of vitamin D supplementation in hospitalized COVID-19 pediatric patients: A randomized controlled trial - Zurita-Cruz, Jessie; Fonseca-Tenorio, Jeffry; Villasís-Keever, Miguel; López-Alarcón, Mardia; Parra-Ortega, Israel; López-Martínez, Briceida; Miranda-Novales, Guadalupe (Frontiers in Pediatrics, 2022)
Background: Some studies suggest that adequate levels of vitamin D (VD) decrease the risk of severe COVID-19. Information about the effectiveness of VD supplementation in children is scarce. Objective: To assess the efficacy and safety of VD supplementation compared to standard of care in hospitalized children with COVID-19. Patients and Methods: Open randomized clinical trial. We included patients from 1 month to 17 years, with moderate COVID-19, who required hospitalization and supplemental oxygen. They were randomized into two groups: VD group, which received doses of 1,000 IU/day (children <1 year) or 2,000 IU/day (from 1 to 17 years), and group without VD (control). The outcome variables were progression of oxygen requirement, development of complications and death. Statistical analysis: For comparison between groups, we used Chi-square or Fisher's exact test, and Mann- Whitney U. Absolute risk reduction (ARR) and number needed to treat (NNT) were calculated. A p-value ≤ 0.05 was considered significant. Results: From March 24, 2020-March 31, 2021, 87 patients were eligible to participate in the trial; 45 were randomized: 20 to the VD group and 25 to the control group. There was no difference in general characteristics at baseline, including serum VD levels (median 13.8 ng/mL in VD group and 11.4 ng/mL in control group). Outcomes: 2/18 (11.1%) in the VD group vs 9/24 (37.5%) in the control group progressed to a superior ventilation modality (p= 0.10), one patient in VD group died (5.5%), compared to 6 (25%) in the control group (p=0.23). ARR was 31.1% (95% CI 8.8 to 60.2%) and NNT 3 (2 to 11), for progression; and 17.93% (95% CI -3.9% to 42.8%) and NNT 6 (2 to 26), for death. None of the patients receiving VD had adverse effects. Trial was stopped for ethical reasons, since after receiving the results of the basal VD values, none of the patients had normal levels. Conclusions: In this trial, VD supplementation in pediatric patients seems to decrease the risk of COVID-19 progression and death. More studies are needed to confirm these findings. The protocol was registered in Clinicaltrials.gov with the number NCT04502667.